VD_FINDINFO 707 vom 27. September 2022 - VD Tribunal cantonal (2022)
DÉTENTION PROVISOIRE, RISQUE DE RÉCIDIVE, RISQUE DE COLLUSION, RISQUE DE FUITE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH), 227 CPP (CH)